Characterization of a novel positive allosteric modulator of the α1A-Adrenergic receptor - Robert S. Papay; Jonathan D. Macdonald; Shaun R. Stauffer; Dianne M. Perez (Elsevier, 2023)
α1-Adrenergic Receptors (ARs) are G-protein Coupled Receptors (GPCRs) that regulate the sympathetic nervous system via the binding and activation of norepinephrine (NE) and epinephrine (Epi). α1-ARs control various aspects of neurotransmission, cognition, cardiovascular functions as well as other organ systems. However, therapeutic drug development for these receptors, particularly agonists, has been stagnant due to unwanted effects on blood pressure regulation. We report the synthesis and characterization of the first positive allosteric modulator (PAM) for the α1-AR based upon the derivation of the α1A-AR selective imidazoline agonist, cirazoline. Compound 3 (Cmpd-3) binds the α1A-AR with high and low affinity sites (0.13pM; 54 ​nM) typical of GPCR agonists, and reverts to a single low affinity site of 100 ​nM upon the addition of GTP. Comparison of Cmpd-3 versus other orthosteric α1A-AR-selective imidazoline ligands reveal unique properties that are consistent with a type I PAM. Cmpd-3 is both conformationally and ligand-selective for the α1A-AR subtype. In competition binding studies, Cmpd-3 potentiates NE-binding at the α1A-AR only on the high affinity state of NE with no effect on the Epi-bound α1A-AR. Moreover, Cmpd-3 demonstrates signaling-bias and potentiates the NE-mediated cAMP response of the α1A-AR at nM concentrations with no effects on the NE-mediated inositol phosphate response. There are no effects of Cmpd-3 on the signaling at the α1B- or α1D-AR subtypes. Cmpd-3 displays characteristics of a pure PAM with no intrinsic agonist properties. Specific derivation of Cmpd-3 at the R1 ortho-position recapitulated PAM characteristics. Our results characterize the first PAM for the α1-AR and holds promise for a first-in-class therapeutic to treat various diseases without the side effect of increasing blood pressure intrinsic to classical orthosteric agonists.